Pengaruh Kecepatan Aliran dan Debit Aliran Terhadap Peningkatan Perolehan Konsentrat Bijih Timah Dalam Tailing Pada Alat Secondary Lobby Box Skala Laboratorium - E.P.S.B Taman Tono; Dede Seiawan; Janiar Pitulima (MINERAL, 2019)
Tailings are the result of the process of mining or processing mineral ore which is considered tohave no economic value. The g in the tailings as evidence that there are losses of cassiterite mineralsthat are also wasted is still of economic value. To reduce losses of cassiterite minerals in tailings, thetool used is the secondary lobby box. The washing of tin tailings was carried out 6 times including theflowrate and the speed of the water flow given differently affected by the opening of the water faucetthat forms the angle of partition on the secondary lobby box. Each of these angles is 15⁰, 30⁰, 45⁰ ,60⁰, 75⁰, and 90⁰. From each experiment a bait was used in the form of tailings with a weight of 5 kgeach (0.47% Sn). At faucet position 15⁰ flow rate of 20.5 l/minute and water flow rate of 0.017 m/secproduced 1.19% Sn and recovery at 76%, position 30⁰ flow rate of 23.5 l/minute and water flow rate of0.020 m/sec produced 1.22% Sn and recovery at 73%, position 45⁰ flow rate of 26 l/minute and waterflow rate of 0.022 m/sec produced 1.25% Sn and recovery at 68%, position 60⁰ flow rate of 28.7l/minute and water flow rate of 0.025 m/sec produced 1.28% Sn and recovery at 65%, position 75⁰flow rate of 32.6 l/minute and water flow rate of 0.028 m/sec produced 1.30% Sn and recovery at53%, and position 90⁰ flow rate of 41 l/min and water flow rate of 0.035 m/sec produced 2.26% Sn andrecovery at 50%. The highest concentration of 2.26% Sn and the desired recovery in the tailingsseparation process is the lowest recovery of 50% in the 90⁰ faucet position. This shows that theprocess of separating products in the form of tailings has increased significantly from the feed contentof 0.47% Sn to 2.26% Sn and transforming tailings products into economically valuable ores.